2019
DOI: 10.1016/j.jsbmb.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D inhibits the epithelial-mesenchymal transition by a negative feedback regulation of TGF-β activity

Abstract: Vitamin D and TGF-β exert opposite effects on epithelial-mesenchymal EMT transition. Here we report a novel mechanism of action of TGF-β that promotes the counteracting activity of vitamin D; in two models of human epithelial-mesenchymal EMT transition we demonstrated for the first time that TGF-β strongly induced the expression of vitamin D receptor (VDR) and that 1,25(OH) 2 D 3 was able to contrast the TGF-β-driven EMT transition by transcriptional modulation. In human bronchial epithelial cells the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 68 publications
10
29
0
1
Order By: Relevance
“…Possibly depending on both genomic (transcriptional) ( 35 ) or non-genomic (stabilization) ( 36 ) mechanisms, equally active after 24 h of treatment, we found that in MPM cell lines calcitriol increased VDR levels and promoted its nuclear translocation. Instead, basal VDR levels were modest in MeT-5A cells and remained unchanged after treatment with calcitriol, which would explain the lack of inhibitory activity in non-malignant cells, in line with previous findings ( 34 ). The induction of the catabolic enzyme 24-hydroxylase may justify the resistance of MeT-5A cells to vitamin D action, and possible differences among cell types, already described in other models ( 19 ), could be discovered also in mesothelial cells in future studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Possibly depending on both genomic (transcriptional) ( 35 ) or non-genomic (stabilization) ( 36 ) mechanisms, equally active after 24 h of treatment, we found that in MPM cell lines calcitriol increased VDR levels and promoted its nuclear translocation. Instead, basal VDR levels were modest in MeT-5A cells and remained unchanged after treatment with calcitriol, which would explain the lack of inhibitory activity in non-malignant cells, in line with previous findings ( 34 ). The induction of the catabolic enzyme 24-hydroxylase may justify the resistance of MeT-5A cells to vitamin D action, and possible differences among cell types, already described in other models ( 19 ), could be discovered also in mesothelial cells in future studies.…”
Section: Discussionsupporting
confidence: 89%
“…Calcitriol was previously found to increase VDR expression in different cancer cells, as well as in bronchial epithelial cells and peritoneal mesothelial cells, along with inhibition of epithelial to mesenchymal transition ( 5 , 8 , 34 ). However, the presence of VDR in MPM cell lines has yet to be examined.…”
Section: Discussionmentioning
confidence: 97%
“…The assay was carried out as previously described [10]. Cells were seeded in a 24-well plate and exposed to the specific frequency of ELF-EMF for 2 days in growth medium; they were then starved overnight again under exposure, with the aim of stopping proliferation.…”
Section: Wound Healing Assaymentioning
confidence: 99%
“…Isoviolanthin, a flavonoid isolated from Dendrobium officinale Kimura et Migo, suppressed TGF‐β1‐induced EMT through inhibiting the TGF‐β1/Smad and phosphatidylinositol 3‐kinase (PI3K)/Akt/mTOR signaling pathways in hepatocellular carcinoma cells . In addition, vitamin D, a well‐known inhibitor of EMT, inhibited EMT by negatively regulating the TGF‐β1 signaling pathway in human bronchial epithelial cells, and MART‐10 (a vitamin D analogue) suppressed metastasis via downregulating EMT in pancreatic cancer cells …”
Section: Small Molecules Against Emtmentioning
confidence: 99%